Exploring reciprocity in perceptions on telecare within the informal carer-care receiver dyad - Hvalič Touzery, Simona (Teorija in praksa, 2021)
Informal carers' telecare acceptance decisions depend on how their care recipients perceive telecare, yet this relationship has not been researched very much. This article draws on qualitative data gathered from informal carers to explore reciprocity in telecare perceptions within dyads of informal carers and care receivers. A 4-month intervention study was conducted from 2018 to 2019 in the Central Slovenia region. A purposive sample of 22 older adults and their informal carers tested two telecare solutions. Thematic analysis was conducted using Atlas.ti 8, with four themes emerging: 1. the benefits of telecare use for older adults; 2. reluctance, rejection or negative perceptions of telecare; 3. the potential violation of older adults' privacy; and 4. the importance of external and internal information for effective telecare use. This study confirms that that telecare perception is dyadically interdependent.
Keywords: diade; Home nursing; neformalna oskrba; Oskrba starostnikov; podporne tehnologije; staranje v domačem okolju; starejše osebe